1995
DOI: 10.1002/app.1995.070580926
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the properties of fibers and thermally bonded nonwoven fabrics made of polypropylene

Abstract: SYNOPSISTypical polypropylene fibers for use in light nonwoven fabrics were produced in a fullscale compact-spinning line. Molecular weight distribution (MWD), extrusion temperature, draw-down ratio, and draw ratio were varied. The fibers were thermally bonded (welded) into nonwoven fabrics, at different bonding temperatures, using a pilot calender line. The tensile properties of the fabrics are influenced by the MWD and the processing conditions of the fibers, and the effects of these fiber parameters increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Of the three available process variables, temperature, pressure and roll speed, only temperature was varied in this work. Prior studies [1,2] had showed pressure was not a particularly important variable in bonding, and roll speed was set to give a commercially realistic contact time of 9 ms. A critical temperature range was identified for each item tested based on scouting experiments, and this range was studied in detail. Fibers used in this work did not seem to stick to the Kraft paper.…”
Section: Bonding Conditionsmentioning
confidence: 99%
“…Of the three available process variables, temperature, pressure and roll speed, only temperature was varied in this work. Prior studies [1,2] had showed pressure was not a particularly important variable in bonding, and roll speed was set to give a commercially realistic contact time of 9 ms. A critical temperature range was identified for each item tested based on scouting experiments, and this range was studied in detail. Fibers used in this work did not seem to stick to the Kraft paper.…”
Section: Bonding Conditionsmentioning
confidence: 99%
“…This process can occur without damaging the structure of the core polymer. A commercial example of a sheath-core fiber is Himont's Moplefan fiber (Andreassen et al, 1995a) which has a polypropylene core and a polyethylene sheath. Jeffries (1971) mentions that sheath-core structures in a single polymer are possible.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Andreassen et al (1995a) studied the interrelationship between fiber properties and nonwoven fabric strength. They theorized that sheath-core differences in melting point could be caused by differences in molecular weight, crystal size, crystal order, and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in strong correlation with the birefringence data. Overall, higher elongations at break are preferred as it leads to homogenous force distribution during bonding [54]. Figure 6 demonstrates the tensile strength of the fibers before bonding and after bonding at different temperatures (145, 150, and 155 � C bonding temperatures).…”
Section: Tensile Propertiesmentioning
confidence: 99%